PAD, Dana Perimbangan, Belanja Modal, SILPA dan Kinerja Keuangan Pemerintah Daerah di Jawa Timur - Ratnasari, Dwi; Meirini, Dianita (E-Jurnal Akuntansi, 2022)
The purpose of the study was to examine the effect of local revenue, balancing funds, capital expenditures and SILPA on the financial performance of local governments as proxied through financial ratios in the form of efficiency ratios. A quantitative approach is used as an approach in this study. Saturated sample for sampling technique. The data analysis technique in this study was a panel data regression test. Based on the results of the T-test, financial performance cannot be affected by local revenue but financial performance can be significantly affected negatively by balancing funds and SILPA, and financial performance can be significantly affected positively by capital expenditures.                Keywords: PAD; Balancing Fund; Capital Expenditures; SILPA; Local Government Financial Performance.